The impact of economics on gold price in India / Nur Intan Solehah Mohd Saufian - Mohd Saufian, Nur Intan Solehah (2022)
Gold has held the attention of mankind. It is one of the most valuable metals discovered to date, as well as the most liquid asset. Since its origin, gold has been the backbone of all economies. Other than that, has been highly prized by nearly all societies. The reasons behind this appear to be self-evident. It's beautiful, its hue and gloss evoke the sun which making it one of the most plausible objects of human devotion, it's highly flexible, and it doesn't corrode. India is the world's greatest consumer of gold. For a considerable number of low and middle-income households in both rural and urban areas, gold is a substantial source of savings. The sharp increasing trend of gold price since the year 2017 had pulled the attention from researchers and investors. In 2017, gold price was only at the RS 26,600, 24 karats per 10 grams and then it had dramatically increased to RS 48,800, 24 karats per 10 grams in 2020. The purpose of this study is to examine the implication of economic determinants on gold price in India. The research is performed using interest rate, consumer price index, exchange rate, and stock market returns. Most of the information for this analysis were collected from the world bank data. This study uses secondary data from India in January 2017 until December 2020. The results of this study are focused on descriptive analysis, correlation analysis, regression analysis, and test assumptions